2016
DOI: 10.1172/jci83658
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation mediates protection from kidney ischemia-reperfusion injury through α7nAChR+ splenocytes

Abstract: ) for measuring NE, the George F. O'Brien Center, University of Alabama (P30DK079337; principal investigator, Anupam Agarwal) for measuring plasma creatinine by LC-MS, the UVA Research Histology Core for their assistance in preparation of histology slides, and the UVA Flow Cytometry Facility for sample analysis using the Luminex 100 IS system and FACS sorting using BD Influx. We also thank Primetech Corp. (Tokyo, Japan) for supplying the iPRECIO microinfusion pump system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
297
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(308 citation statements)
references
References 56 publications
7
297
2
2
Order By: Relevance
“…12). Interorgan trafficking of immune cells and dissemination of inflammatory cytokines are surely responsible for many of these effects, but the present study by Inoue, Abe et al again reinforces the view that neural mechanisms are also likely to contribute in important ways to this phenomenon (5). Indeed, in the course of their study, the authors replicated the previous observation (13) that renal sympathetic denervation profoundly decreases injury in one model of IRI.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…12). Interorgan trafficking of immune cells and dissemination of inflammatory cytokines are surely responsible for many of these effects, but the present study by Inoue, Abe et al again reinforces the view that neural mechanisms are also likely to contribute in important ways to this phenomenon (5). Indeed, in the course of their study, the authors replicated the previous observation (13) that renal sympathetic denervation profoundly decreases injury in one model of IRI.…”
Section: Discussionsupporting
confidence: 88%
“…Unfortunately, the ability of such an approach to treat AKI that has already started to progress is not a likely outcome, as the protective effect of neuroimmunomodulation only developed after a significant delay -VNS was effective at attenuating AKI when delivered at 24 hours but not at 2 hours prior to injury (5). Therefore, the most likely clinical use for this approach would be as a prophylactic measure in situations where the patient is at high risk of developing AKI.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, animal models have shown that the spleen may play a key role in orchestrating signals from the vagus nerve to the immune system [84]. Adoptive transfer of a7nAChR-positive splenocytes from VNS-treated wild-type mice, but not from a7nAChR-knockout mice, protected against kidney ischaemia-reperfusion injury [85], indicating a role for the a7nAChR in this mechanism. Another study showed that VNS may result in reduced expression of IL-6 and TNF in the brain of rats after LPS injection into the trachea, specifically in the nucleus tractus solitarii where the afferent vagus nerve terminates, indicating that VNS could also change cytokine expression centrally [86].…”
Section: The Effects Of Vagus Nerve Stimulation On Inflammation In Humentioning
confidence: 83%
“…Burne-Taney et al [29] reported that nu/nu mice receiving spleen derived leukocytes from ischemic wild-type mice had significantly reduced renal injury compared with nu/nu mice receiving leukocytes from sham-operated, wild-type mice. Inoue et al [30] demonstrated that the renoprotective effects and the anti-inflammatory properties mediated by the stimulation of the vagus nerves depended on α7 nicotinic acetylcholine receptors-positive splenocytes. Andrés-Hernando et al [31] demonstrated that splenectomy exacerbated the proinflammatory response that occurred in ischemic AKI by removal of the anti-inflammatory cytokine IL-10.…”
Section: Discussionmentioning
confidence: 99%